Optimization Of Vehicle Flow Patterns In Sape Port, Bima Provinsi, West Nusa Tenggara Province - Kodrat Alam; Broto Priyono; Muhammad Dwi Cahyo (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2021)
Sape Port is a port managed by PT. ASDP Indonesia Ferry (Persero) Sape Branch. At this time at the Sape Crossing Port there are still several shortcomings because there are still many people and unauthorized vehicles that can easily enter the port area, causing the port to become less orderly, there are still crossings between vehicles that will enter the ship and vehicles those who get out of the ship, and hawkers selling their goods in the area around the pier. This is due to the absence of a zoning system that is in accordance with the Minister of Transportation Regulation Number 29 of 2016 concerning the Sterilization of Ferry Ports. So that in the activity of getting on and off of passengers and loading and unloading vehicles, there are several obstacles, including the absence of zoning implementation at the port which causes unauthorized people to enter prohibited areas, and the mixing of passengers and vehicles when getting on or off the ship. To analyze this, refer to the Regulation of the Minister of Transportation Number 29 of 2016 concerning the Sterilization of Ferry Ports and SK.242 / HK.104 / DRJD / 2010 concerning Technical Guidelines for Ferry Traffic Management. The analysis used is zoning analysis, analysis of equipment that supports the zone system, and analysis of vehicle flow patterns. In order to smoothen the flow of cargo traffic both entering the port area and cargo going out of the Ferry Port area, namely by implementing a zoning system based on the Minister of Transportation Regulation Number 29 of 2016 concerning Ferry Port Sterilization and regulation of traffic flow patterns in accordance with SK.242 /HK.104/DRJD/2010 concerning Technical Guidelines for Pedestrian Traffic Management and adding equipment that supports the zone system such as signs needed to support safety and comfort. The desired pattern of vehicle movement is to rearrange the lanes of vehicles that leave and enter the ship so that the delivery / pick-up does not enter the prohibited area and assign officers to regulate traffic so that it runs more orderly. To regulate passenger movement patterns so as not to mix with vehicles that would endanger the safety of passengers and vehicles.